Endoscopic intermuscular dissection for deep submucosal invasive cancer in the rectum: a new endoscopic approach - Moons, Leon M. G.; Bastiaansen, Barbara A. J.; Richir, Milan C.; Hazen, Wouter L.; Tuynman, Jurriaan; Elias, Sjoerd G.; Schrauwen, Ruud W M.; Vleggaar, Frank P.; Dekker, Evelien; Bos, Philip; Fariña Sarasqueta, Arantza; Lacle, Miangela; Hompes, Roel; Didden, Paul (Endoscopy, 2022)
Background The risk of lymph node metastasis associated with deep submucosal invasion should be balanced against the mortality and morbidity of total mesorectal excision (TME). Dissection through the submucosa hinders radical deep resection, and full-thickness resection may influence the outcome of completion TME. Endoscopic intermuscular dissection (EID) in between the circular and longitudinal part of the muscularis propria could potentially provide an R0 resection while leaving the rectal wall intact.Methods In this prospective cohort study, the data of patients treated with EID for suspected deep submucosal invasive rectal cancer between 2018 and 2020 were analyzed. Study outcomes were the percentages of technical success, R0 resection, curative resection, and adverse events.Results 67 patients (median age 67 years; 73 % men) were included. The median lesion size was 25 mm (interquartile range 20–33 mm). The rates of overall technical success, R0 resection, and curative resection were 96 % (95 %CI 89 %–99 %), 81 % (95 %CI 70 %–89 %), and 45 % (95 %CI 33 %–57 %). Only minor adverse events occurred in eight patients (12 %).Conclusion EID for deep invasive T1 rectal cancer appears to be feasible and safe, and the high R0 resection rate creates the potential of rectal preserving therapy in 45 % of patients.